Managing Conflicts with Wildlife: Living with Panthers - William M. Giuliano; Holly K. Ober; Lauren Watine; Raoul Boughton; Eric Hellgren; Darrell Land; Mark Lotz (EDIS)
Panthers help maintain populations of some native species and control nuisance species such as wild hogs. They are generally secretive and rarely bother people, but there are rare situations where panthers can become dangerous or damaging. In this 4-page fact sheet, we present some facts about panthers, describe dangers and problems they may cause, and provide suggestions on how to cope with these issues. Written by William M. Giuliano, Holly K. Ober, Lauren Watine, Raoul Boughton, Eric Hellgren, Darrell Land, and Mark Lotz, and published by the UF Department of Wildlife Ecology and Conservation, April 2015.